Energy transfer in two-wave mixing quasi-degenerated in photorefractive crystals - Barrera, B. (2016)
Wave equations describing the quasi-degenerated two-beam coupling in the photorefractive crystals for high frequency gratings have been solved. In the case of the quasi-degenerate two-beam coupling, equations depend upon the coupling coefficient, the response time of the medium, the input beams frequencies, the absorption coefficient and the input intensity ratio. The response time of the medium is function of the diffusion field, the drift field, the saturation field and the concentration ratio, i.e., the ratio between NA density of acceptor impurities and ND density of donor impurities. The effect of these parameters on the gain has been studied in details.